ANALISIS PENGARUH KEKERASAN KARET TERHADAP SENSOR WEIGHT IN MOTION (WIM) BERBASIS SERAT OPTIK - Delimasari, Desi; Tjahyo Baskoro, Winardi; Hanto, Dwi (BULETIN FISIKA, 2015)
Conducted a research on the analysis of the effect of rubber hardness on the capacity of the sensor Weight In Motion (WIM). Observation conducted on the sensors WIM using microbending techniques, multimode optical fiber and stable laser source with a wavelength of 1610 nm. This research using rubbers with hardness is 40 kN/mm, 50 kN/mm and 60 kN/mm . Research capacity of the sensor WIM with compression test using UTM (Universal Testing Machine) in static state. The result showed that the sensors WIM is faster response for rubber hardness 60 kN/mm with a capacity of 770 N. Whereas the maximum load of 3485 N in rubber hardness 40 kN/mm, so the rubber with a hardness of 40 kN/mm is good use in applying sensors WIM to control and detect the vehicle load with overload. Keywords : Rubber, sensors capasity, Weight In Motion, microbending, multimode optical fiber, static